Artificial leather and manufacturing method thereof

By using water-dispersed polyurethane with hydrophilic groups in artificial leather, and adjusting its mass retention rate and weight average molecular weight of dissolved components in N,N-dimethylformamide, and improving the fiber complexity of the fibrous substrate, the problem of difficulty in achieving efficient manufacturing and taking into account both soft feel and durability in the prior art is solved, and an efficient, soft and wear-resistant artificial leather is achieved.

CN119895095APending Publication Date: 2025-04-25TORAY INDUSTRIES INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380060836.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-31
Filing Date
2023-10-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, it is difficult to achieve efficient manufacturing and take into account both soft feel and excellent durability when manufacturing artificial leather.

Method used

Artificial leather is made by using a water-dispersed polyurethane with hydrophilic groups and adjusting the mass retention rate after impregnation in N,N-dimethylformamide and the weight average molecular weight of the dissolved components within a specific range, and combined with the improvement of fiber complexity in the fibrous substrate.

Benefits of technology

It realizes the soft feel of artificial leather and excellent wear resistance, improves manufacturing efficiency, and has good durability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005277873990000361
    Figure BDA0005277873990000361
  • Figure BDA0005277873990000371
    Figure BDA0005277873990000371
  • Figure BDA0005277873990000381
    Figure BDA0005277873990000381
Patent Text Reader

Abstract

The artificial leather comprises, as constituent elements, a fibrous base material comprising polyester ultrafine fibers having an average single fiber diameter of 0.1 [mu] m to 10.0 [mu] m, and a polyurethane having a hydrophilic group, the content ratio of the polyurethane having a hydrophilic group in the artificial leather being 15 mass% to 25 mass%, the mass retention rate of the polyurethane having a hydrophilic group after the artificial leather is immersed in N, N-dimethylformamide at 25 DEG C for 24 hours is 50-80% by mass, and the mass retention rate of the polyurethane having a hydrophilic group after the artificial leather is immersed in N, N-dimethylformamide at 25 DEG C for 24 hours is 50-80% by mass, and the mass retention rate of the polyurethane having a hydrophilic group after the artificial leather is immersed in N, N-dimethylformamide at 25 DEG C for 24 hours is 50-80% by mass. The weight-average molecular weight of the components dissolved in the N, N-dimethylformamide is from 50,000 to 100,000 (inclusive). Provided are: an artificial leather which is an environmentally friendly process without using an organic solvent and which has both a soft texture and excellent durability; and a method for producing the artificial leather.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to artificial leather and a method for producing the same. Background Art

[0002] Artificial leather, which mainly includes a fiber base material such as non-woven fabric and polyurethane, has excellent characteristics that natural leather does not have, and its use in clothing, furniture, and vehicle interior decoration materials is expanding year by year. In addition, when manufacturing such artificial leather, a method of using a more environmentally friendly water-dispersible polyurethane prepared by dispersing a polyurethane resin in water is being studied instead of the conventional method of using polyurethane based on an organic solvent.

[0003] Hitherto, several methods for obtaining such artificial leather have been proposed.

[0004] For example, Patent Document 1 proposes a method of adding a specific amount of polyvinyl alcohol having a specific saponification degree and a specific polymerization degree to a fibrous substrate, adding a water-dispersible polyurethane, and then removing the polyvinyl alcohol. It is also described that this method can obtain a sheet-like article having a beautiful appearance and a soft feel and good wear resistance.

[0005] In addition, Patent Document 2 proposes a method including, in sequence, impregnating a fibrous substrate including ultrafine fiber-developing fibers with an aqueous dispersion containing a specific macromolecular elastic body, a specific amount of an inorganic salt containing a monovalent cation, and a crosslinking agent, followed by a macromolecular elastic body impregnation step, an ultrafine fiber-developing step, a drying step, and a raising step. It is also described that this method can produce a sheet-like article having both a soft feel and excellent light resistance.

[0006] Patent Document 3 proposes a method of impregnating and fixing polyurethane in an aqueous emulsion before and after removing the sea component from the sea-island type composite fiber. It is also described that this method can produce a suede-like ultrafine fiber nonwoven fabric having the best physical and mechanical properties, abrasion resistance and appearance.

[0007] Furthermore, Patent Document 4 proposes a method of performing a polymer elastomer impregnation step in which a fibrous substrate including ultrafine fiber-developing fibers is impregnated with an aqueous dispersion containing a specific polymer elastomer, a specific amount of an inorganic salt containing a monovalent cation, and a crosslinking agent before and after the ultrafine fiber-developing step, and then heat-treating the fiber at a specific temperature. It is also described that a sheet-like article having excellent softness, chemical resistance, and dyeing resistance can be obtained according to this method.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: International Publication No. 2014 / 042241

[0011] Patent Document 2: International Publication No. 2021 / 125032

[0012] Patent Document 3: Japanese Patent Application Publication No. 2003-306878

[0013] Patent Document 4: International Publication No. 2021 / 125029 Summary of the invention

[0014] Problems to be solved by the invention

[0015] In the method disclosed in Patent Document 1, a soft feel and durability are achieved simultaneously by appropriately adjusting the bonding state between polyurethane and ultrafine fibers. However, since a dissolution treatment of polyvinyl alcohol is required, there is still room for improvement in production efficiency.

[0016] In the method disclosed in Patent Document 2, the bonding state between polyurethane and ultrafine fibers is moderately relaxed, and a soft feel is achieved even without adding polyvinyl alcohol. However, from the perspective of durability represented by abrasion resistance, there is still room for improvement.

[0017] In the methods disclosed in Patent Documents 3 and 4, both soft feel and durability are achieved by applying polyurethane twice. However, since polyurethane is applied in two stages, there is still room for improvement in production efficiency.

[0018] Therefore, in view of the above problems, an object of the present invention is to provide an artificial leather and a method for producing the same which is an environmentally friendly process that does not use an organic solvent and which can achieve both a soft touch and excellent durability.

[0019] Means for solving problems

[0020] In order to achieve the above-mentioned purpose, the inventor of the present application has repeatedly studied and found that by using a polyurethane with a hydrophilic group as a water-dispersible polyurethane in artificial leather, and then adjusting the mass retention rate of the polyurethane with a hydrophilic group after being immersed in N,N-dimethylformamide (hereinafter, sometimes referred to as DMF) and the weight average molecular weight of the component dissolved in DMF in a specific range, the softness and wear resistance of the artificial leather can be taken into account at a high level. In addition, it is found that in the manufacturing process, when the entanglement degree of the fiber in the fibrous substrate is increased to a specific range, the artificial leather has higher durability.

[0021] The present invention has been completed based on these findings, and according to the present invention, the following inventions can be provided.

[0022] [1] An artificial leather comprising a fibrous substrate composed of polyester ultrafine fibers having an average single fiber diameter of 0.1 μm to 10.0 μm, and a polyurethane having a hydrophilic group as constituent elements, wherein the content of the polyurethane having a hydrophilic group in the artificial leather is 15% by mass to 25% by mass, the mass retention rate of the polyurethane having a hydrophilic group after immersing the artificial leather in N,N-dimethylformamide at 25°C for 24 hours is 50% by mass to 80% by mass, and the weight average molecular weight of a component dissolved in N,N-dimethylformamide after immersing the artificial leather in N,N-dimethylformamide at 25°C for 24 hours is 50,000 to 100,000.

[0023] [2] The artificial leather according to [1], wherein the apparent density of the artificial leather is 0.30 g / cm 3 Above 0.40g / cm 3 the following.

[0024] [3] The artificial leather according to [1] or [2], wherein the polyurethane having a hydrophilic group contains a constituent component derived from a polyester polyol.

[0025] [4] The artificial leather according to [3], wherein the polyurethane having a hydrophilic group further contains a constituent component derived from a polycarbonate polyol.

[0026] [5] The artificial leather according to any one of [1] to [4], wherein the polyurethane having a hydrophilic group has an N-acylurea bond and / or an isourea bond.

[0027] [6] The method for producing artificial leather according to any one of [1] to [5], comprising the following steps (1) to (4) in order:

[0028] Step (1): performing an entanglement treatment on a nonwoven fabric containing ultrafine fiber-developing fibers so that the density change rate before and after the entanglement becomes 2.5 times or more and 3.5 times or less to form a fibrous substrate;

[0029] Step (2): impregnating the fibrous substrate with an aqueous dispersion containing a polyurethane precursor having a weight average molecular weight of 50,000 to 100,000 and a crosslinking agent, and then performing a heat drying treatment to form an impregnated sheet containing the fibrous substrate and the polyurethane having a hydrophilic group as constituent elements;

[0030] Step (3): allowing the polyester ultrafine fibers to emerge from the ultrafine fiber-emerging fibers of the impregnated sheet to form a pre-heat-treated sheet comprising a fibrous substrate composed of the polyester ultrafine fibers and the polyurethane having a hydrophilic group as constituent elements;

[0031] Step (4): heat-treating the pre-heat-treatment sheet at an ambient temperature of 150° C. to 200° C. for 5 minutes to 20 minutes.

[0032] [7] The method for producing artificial leather according to [6], wherein the cross-linking agent is a carbodiimide-based cross-linking agent.

[0033] [8] The method for producing artificial leather according to [6] or [7], wherein in the step (1), silicone is added in an amount of 0.01% by mass to 3% by mass relative to the mass of the ultrafine fiber-developing fiber.

[0034] Effects of the Invention

[0035] According to the present invention, it is possible to obtain artificial leather having both a soft texture and excellent abrasion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] [ Figure 1 ] Figure 1 This is a conceptual cross-sectional view for explaining a method for measuring the average pile length of the artificial leather of the present invention. DETAILED DESCRIPTION

[0037] The artificial leather of the present invention is an artificial leather comprising a fibrous substrate composed of polyester ultrafine fibers having an average single fiber diameter of 0.1 μm to 10.0 μm, and a polyurethane having a hydrophilic group as constituent elements, wherein the content of the polyurethane having a hydrophilic group in the artificial leather is 15% by mass to 25% by mass, the mass retention rate of the polyurethane having a hydrophilic group after immersing the artificial leather in N,N-dimethylformamide at 25° C. for 24 hours is 50% by mass to 80% by mass, and the weight average molecular weight of a component dissolved in N,N-dimethylformamide after immersing the artificial leather in N,N-dimethylformamide at 25° C. for 24 hours is 50,000 to 100,000.

[0038] Hereinafter, the above-mentioned components will be described in detail. However, the present invention is not limited to the scope of the following description unless it exceeds the gist of the present invention. Various changes can be made within the scope of the gist of the present invention.

[0039] [Polyester ultra-fine fiber]

[0040] Regarding the artificial leather of the present invention, the fibrous base material as one of the constituent elements is composed of polyester ultrafine fibers having an average single fiber diameter of 0.1 μm or more and 10.0 μm or less. It should be noted that the so-called "polyester ultrafine fibers" refer to ultrafine fibers containing the following polyester resins, and the so-called ultrafine fibers refer to "fibers having a single fiber diameter of 0.1 μm or more and 10.0 μm or less" measured and calculated by the method described below.

[0041] It should be noted that, in the present invention, the so-called "polyester resin" refers to a resin in which the molar fraction of polyester units in the repeating units is 80 mol% to 100 mol%. Unless otherwise specified, the substance recorded as "··· resin" is also the same. The polyester resin can be made into artificial leather with excellent heat resistance, light resistance, etc., and as a specific example, polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, and mixtures and copolymers of these polyester resins can be cited. Polyester resins can be obtained, for example, using dicarboxylic acids and / or their ester-forming derivatives and diols as raw materials.

[0042] As the dicarboxylic acid and / or its ester-forming derivative used in the polyester resin, terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, diphenyl-4,4'-dicarboxylic acid and its ester-forming derivatives, etc. can be cited. It should be noted that the so-called ester-forming derivatives in the present invention refer to lower alkyl esters, acid anhydrides, acid chlorides, etc. of dicarboxylic acids. Specifically, methyl esters, ethyl esters, hydroxyethyl esters, etc. can be preferably used. As the dicarboxylic acid and / or its ester-forming derivative used in the present invention, a more preferred embodiment is terephthalic acid and / or its dimethyl ester.

[0043] Examples of the diol used for the polyester resin include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, and cyclohexanedimethanol. Among them, ethylene glycol is preferably used.

[0044] Furthermore, the polyester resin may contain inorganic particles such as titanium oxide particles, a lubricant, a pigment, a heat stabilizer, an ultraviolet absorber, a conductive agent, a heat storage agent, an antibacterial agent, and the like, depending on various purposes.

[0045] The content of the components other than the polyester resin that can be contained in the polyester resin is preferably 3% by mass or less, more preferably 1.5% by mass or less in the polyester resin. By making the content of the components other than the polyester resin 3% by mass or less, the strength of the polyester ultrafine fiber can be suppressed from decreasing, and an artificial leather having excellent wear resistance can be obtained.

[0046] The cross-sectional shape of the polyester ultrafine fiber may be a circular cross-sectional shape or a special cross-sectional shape. Specific examples of the special cross-sectional shape include an elliptical, flat, polygonal shape such as a triangle, a fan-shaped shape, and a cross-shaped shape.

[0047] In the present invention, the average single fiber diameter of the polyester ultrafine fiber is 0.1 μm to 10.0 μm. By making the average single fiber diameter of the polyester ultrafine fiber less than 10.0 μm, preferably less than 7.0 μm, and more preferably less than 5.0 μm, the artificial leather can be made softer. In addition, the quality of the pile can be improved. On the other hand, by making the average single fiber diameter of the polyester ultrafine fiber more than 0.1 μm, preferably more than 0.3 μm, and more preferably more than 0.7 μm, when dyeing is performed, an artificial leather with excellent color development after dyeing can be produced. In addition, when the pile treatment using polishing is performed, the dispersibility and fluffiness of the polyester ultrafine fibers in bundles can be improved.

[0048] It should be noted that the single fiber diameter and average single fiber diameter of the polyester ultrafine fiber in the present invention are measured and calculated by the following method. That is,

[0049] (1) A cross section of the obtained artificial leather cut in the thickness direction is observed at a magnification of 1000 times using a scanning electron microscope (SEM, for example, "VHX-D500 / D510" manufactured by KEYENCE CORPORATION).

[0050] (2) The single fiber diameters of 50 arbitrary polyester ultrafine fibers within the observation surface are measured in three directions in the cross section of each polyester ultrafine fiber. In the case of using polyester ultrafine fibers with a special cross section, the cross-sectional area of ​​the single fiber is first measured, and the diameter of the circle that forms the cross-sectional area is calculated by the following formula. The diameter thus obtained is taken as the single fiber diameter of the single fiber.

[0051] Single fiber diameter (μm) = (4 × (single fiber cross-sectional area (μm) 2 )) / π) 1 / 2

[0052] (3) The arithmetic mean value (μm) of the single fiber diameters of the 150 points obtained as described above was calculated, and the second decimal place was rounded off to the nearest integer, and the result was taken as the average single fiber diameter (μm) of the polyester ultrafine fibers.

[0053] [Fiber base material]

[0054] The fibrous substrate used in the present invention is composed of the polyester ultrafine fibers. It should be noted that the fibrous substrate may contain a mixture of polyester ultrafine fibers made of different materials.

[0055] As a specific embodiment of the fibrous substrate, a nonwoven fabric formed by entanglement of the polyester ultrafine fibers, a nonwoven fabric formed by entanglement of fiber bundles of polyester ultrafine fibers, etc. can be used. Among them, from the perspective of strength and feel of artificial leather, a nonwoven fabric formed by entanglement of fiber bundles of polyester ultrafine fibers can be preferably used. From the perspective of softness and feel, it is particularly preferred to use a nonwoven fabric in which the polyester ultrafine fibers constituting the fiber bundles of polyester ultrafine fibers are appropriately separated from each other and have gaps of 1μm to 100μm. In this way, the nonwoven fabric formed by entanglement of fiber bundles of polyester ultrafine fibers can be obtained by, for example, entanglement of ultrafine fiber-revealing fibers in advance and then making the polyester ultrafine fibers visible. In addition, a nonwoven fabric in which the polyester ultrafine fibers constituting the fiber bundles of polyester ultrafine fibers are appropriately separated from each other and have gaps can be obtained by, for example, using sea-island type composite fibers (the sea-island type composite fibers can form gaps between island components by removing sea components).

[0056] The nonwoven fabric may be any of short-fiber nonwoven fabric and long-fiber nonwoven fabric, and short-fiber nonwoven fabric is more preferably used from the viewpoint of the feel and quality of the artificial leather. It should be noted that the so-called short-fiber nonwoven fabric refers to a nonwoven fabric composed mainly of fibers having a fiber length of less than 1000 mm.

[0057] When a short-fiber nonwoven fabric is used, the fiber length of the fibers constituting the short-fiber nonwoven fabric is preferably in the range of 25 mm to 90 mm. By making the fiber length 25 mm or more, more preferably 35 mm or more, and further preferably 40 mm or more, it is easy to obtain an artificial leather having excellent wear resistance due to entanglement. In addition, by making the fiber length 90 mm or less, more preferably 80 mm or less, and further preferably 70 mm or less, it is possible to obtain an artificial leather having a better feel and quality.

[0058] In the present invention, when a nonwoven fabric is used as the fibrous substrate, a woven fabric or a knitted fabric may be inserted, layered, or lined inside the nonwoven fabric for the purpose of improving strength, etc. Since damage during entanglement can be suppressed and strength can be maintained, the average single fiber diameter of the fibers constituting the woven fabric or the knitted fabric is preferably 0.3 μm or more and 10 μm or less.

[0059] In addition, when the fibers constituting the woven fabric or knitted fabric are multifilaments, the total fineness of the multifilaments is preferably 30 dtex or more and 170 dtex or less. By making the total fineness of the multifilaments constituting the woven fabric or the like 170 dtex or less, more preferably 150 dtex or less, an artificial leather having excellent softness can be obtained. On the other hand, by making the total fineness 30 dtex or more, not only the morphological stability of the product as the artificial leather is improved, but also when the non-woven fabric and the woven fabric or the like are entangled and integrated by needle punching or the like, the fibers constituting the woven fabric or the like are not easily exposed on the surface of the artificial leather, so it is preferred. At this time, with respect to the woven fabric, the total fineness of the multifilaments of the warp yarn and the weft yarn may be the same or different.

[0060] In the present invention, the total fineness of the multifilament refers to a value measured and calculated by "8.3 Fineness" "8.3.1 Gross fineness b) Method B (Simplified method)" of JIS L1013:2010 "Testing methods for chemical filaments".

[0061] As fibers constituting the woven fabric and knitted fabric, synthetic fibers such as polyesters such as polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, and polylactic acid, polyamides such as polyamide 6 and polyamide 66, regenerated fibers such as cellulose polymers, and natural fibers such as cotton and linen can be used.

[0062] The apparent density of the fibrous substrate of the artificial leather of the present invention is preferably 0.25 g / cm 3 Above 0.30g / cm 3 The apparent density of the fibrous substrate is set to a lower limit of 0.25 g / cm 3 More preferably, 0.26 g / cm 3 On the other hand, regarding the above range, by making its upper limit 0.30 g / cm 3 Below, more preferably 0.28g / cm 3 Thus, polyurethane having a hydrophilic group is uniformly imparted, and artificial leather having excellent resilience can be obtained. In the present invention, the apparent density of the fibrous substrate is calculated by the following formula.

[0063] Apparent density of fibrous substrate (g / cm 3 ) = apparent density of artificial leather (g / cm 3 )×Ratio of fibrous base material in artificial leather (%)

[0064] Here, the fiber base material ratio (%) in the artificial leather refers to the ratio of the mass reduced by extraction when only the polyester ultrafine fibers of the artificial leather are extracted with a solvent, with the mass of the artificial leather being taken as 100%.

[0065] [Polyurethane having hydrophilic groups]

[0066] Next, the artificial leather of the present invention includes polyurethane having a hydrophilic group as a constituent element, which will be described in further detail below.

[0067] (1) Polyurethane with hydrophilic groups

[0068] First, the "hydrophilic group" in the present invention refers to a "group having active hydrogen". Specific examples of the group having active hydrogen include a hydroxyl group, a carboxyl group, a sulfonic acid group, an amino group, etc. From the viewpoint of reactivity with a cross-linking agent having a carbodiimide group described later, a hydroxyl group or a carboxyl group is preferred.

[0069] The polyurethane having a hydrophilic group can be obtained by reacting a polymer polyol, an organic diisocyanate, and a compound having an active hydrogen component having a hydrophilic group described below to form a hydrophilic prepolymer, then adding a chain extender and reacting them to obtain a polyurethane precursor, and reacting the polyurethane precursor with a crosslinking agent. This will be described in detail below.

[0070] (1-1) Polyols

[0071] Examples of the polymer polyol preferably used in the present invention include polyether polyol, polyester polyol, polycarbonate polyol and the like.

[0072] First, examples of polyether polyols include polyols obtained by addition polymerization of monomers such as ethylene oxide, propylene oxide, butylene oxide, styrene oxide, tetrahydrofuran, epichlorohydrin, and cyclohexene using polyols and polyamines as initiators, and polyols obtained by ring-opening polymerization of the above monomers using protonic acids, Lewis acids, and cationic catalysts as catalysts. Specifically, examples include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, and the like, and copolyols obtained by combining these.

[0073] Next, examples of the polyester polyol include polyester polyols obtained by condensing various low molecular weight polyols with polybasic acids, polyols obtained by opening polymerization of lactones, and the like.

[0074] Examples of the low molecular weight polyol used in the polyester polyol include one or more selected from linear alkylene glycols such as ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol, branched alkylene glycols such as neopentyl glycol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, and 2-methyl-1,8-octanediol, alicyclic diols such as 1,4-cyclohexanediol, and aromatic diols such as 1,4-bis(β-hydroxyethoxy)benzene. In addition, adducts obtained by adding various alkylene oxides to bisphenol A can also be used as the low molecular weight polyol.

[0075] On the other hand, examples of the polyacid used in the polyester polyol include one or more selected from the group consisting of succinic acid, maleic acid, adipic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, phthalic acid, isophthalic acid, terephthalic acid, and hexahydroisophthalic acid.

[0076] Examples of the polycarbonate polyol include compounds obtained by reaction of a polyol with a carbonate compound, such as a polyol with a dialkyl carbonate or a polyol with a diaryl carbonate.

[0077] As the polyol used in the polycarbonate polyol, a low molecular weight polyol used in the polyester polyol can be used. On the other hand, as the dialkyl carbonate, dimethyl carbonate, diethyl carbonate, etc. can be used, and as the diaryl carbonate, diphenyl carbonate, etc. can be used.

[0078] It should be noted that the number average molecular weight of the polymer polyol preferably used in the present invention is preferably 500 to 5000. By making the number average molecular weight of the polymer polyol 500 or more, more preferably 1500 or more, it is easy to prevent the feel of the artificial leather from becoming hard. In addition, by making the number average molecular weight 5000 or less, more preferably 4000 or less, it is easy to maintain the strength of the polyurethane with a hydrophilic group as a binder.

[0079] (1-2) Organic diisocyanate

[0080] The organic diisocyanate used in the present invention includes aromatic diisocyanates having 6 to 20 carbon atoms (excluding carbon in the NCO group, the same applies hereinafter), aliphatic diisocyanates having 2 to 18 carbon atoms, alicyclic diisocyanates having 4 to 15 carbon atoms, aromatic aliphatic diisocyanates having 8 to 15 carbon atoms, modified forms of these diisocyanates (carbodiimide modified forms, urethane modified forms, uretdione modified forms, etc.), and mixtures of two or more thereof.

[0081] Specific examples of the aromatic diisocyanate having 6 to 20 carbon atoms include 1,3- and / or 1,4-phenylene diisocyanate, 2,4- and / or 2,6-toluene diisocyanate, 2,4'- and / or 4,4'-diphenylmethane diisocyanate (hereinafter referred to as MDI), 4,4'-biphenyl diisocyanate, 3,3'-dimethyl-4,4'-biphenyl diisocyanate, 3,3'-dimethyl-4,4'-diphenylmethane diisocyanate, and 1,5-naphthalene diisocyanate. Among them, MDI is preferably used because it has excellent flexibility when forming a polyurethane having a hydrophilic group.

[0082] Specific examples of the aliphatic diisocyanate having 2 to 18 carbon atoms include ethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, dodecamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, 2,6-diisocyanatomethylhexanoate, bis(2-isocyanatoethyl)carbonate, and 2-isocyanatoethyl-2,6-diisocyanatohexanoate.

[0083] Specific examples of the alicyclic diisocyanate having a carbon number of 4 to 15 include isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, bis(2-isocyanatoethyl)-4-cyclohexylene-1,2-dicarboxylate, and 2,5- and / or 2,6-norbornane diisocyanate, etc. Among them, dicyclohexylmethane-4,4'-diisocyanate is preferably used because it has excellent durability when forming a polyurethane having a hydrophilic group.

[0084] Specific examples of the aromatic aliphatic diisocyanate having 8 to 15 carbon atoms include m-xylylene diisocyanate and / or p-xylylene diisocyanate, and α,α,α′,α′-tetramethylxylylene diisocyanate.

[0085] (1-3) Compounds containing active hydrogen components having a hydrophilic group

[0086] As the compound containing active hydrogen component having a hydrophilic group preferably used in the present invention, there can be mentioned compounds containing active hydrogen and one or more groups selected from nonionic groups, anionic groups and cationic groups. These compounds containing active hydrogen components can also be used in the state of salts obtained by neutralization with a neutralizing agent. By using the compound containing active hydrogen component having a hydrophilic group, the stability of the aqueous dispersion used in the method for producing artificial leather described later can be improved.

[0087] Examples of the compound having a nonionic group and active hydrogen include compounds containing two or more active hydrogen components or two or more isocyanate groups and having a polyoxyethylene glycol group having a molecular weight of 250 to 9000 in a side chain, and triols such as trimethylolpropane and trimethylolbutane.

[0088] Examples of the compound having an anionic group and active hydrogen include carboxyl group-containing compounds such as 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, and 2,2-dimethylolvaleric acid, and derivatives thereof; sulfonic acid group-containing compounds such as 1,3-phenylenediamine-4,6-disulfonic acid and 3-(2,3-dihydroxypropoxy)-1-propanesulfonic acid, and derivatives thereof; and salts obtained by neutralizing the above compounds with a neutralizing agent.

[0089] Examples of the compound containing a cationic group and active hydrogen include tertiary amino group-containing compounds such as 3-dimethylaminopropanol, N-methyldiethanolamine, and N-propyldiethanolamine, and derivatives thereof.

[0090] (1-4) Chain Extender

[0091] Examples of the chain extender used in the present invention include water, low molecular weight diols such as ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, diethylene glycol and neopentyl glycol, alicyclic diols such as 1,4-bis(hydroxymethyl)cyclohexane, aromatic diols such as 1,4-bis(hydroxyethyl)benzene, aliphatic diamines such as ethylenediamine, alicyclic diamines such as isophoronediamine, aromatic diamines such as 4,4-diaminodiphenylmethane, aromatic aliphatic diamines such as xylylenediamine, alkanolamines such as ethanolamine, hydrazine, dihydrazides such as adipic acid dihydrazide, and mixtures of two or more thereof.

[0092] Among the above, a preferred chain extender is selected from water, low molecular weight diols and aromatic diamines, and a more preferred chain extender is selected from water, ethylene glycol, 1,4-butanediol, 4,4'-diaminodiphenylmethane and a mixture of two or more thereof.

[0093] (1-5) Composition of polyurethane precursor

[0094] As described above, the polyurethane precursor used in the present invention is prepared by reacting the polymer polyol, organic diisocyanate, and a compound containing an active hydrogen component having a hydrophilic group to form a hydrophilic prepolymer, and then adding a chain extender and reacting them.

[0095] (1-6) Cross-linking agent

[0096] As the crosslinking agent used in the present invention, a crosslinking agent having two or more reactive groups in the molecule that can react with the reactive group introduced into the polyurethane precursor can be used. Specifically, polyisocyanate crosslinking agents such as water-soluble isocyanate compounds and blocked isocyanate compounds, melamine crosslinking agents, carbodiimide crosslinking agents, etc. can be cited. The crosslinking agent can be used alone or in combination of two or more.

[0097] The water-soluble isocyanate compound is a compound having two or more isocyanate groups in the molecule, and examples thereof include the above-mentioned organic diisocyanate compounds, etc. Commercially available products include "Bayhydur" (registered trademark) series and "Desmodur" (registered trademark) series manufactured by Bayer Material Science Co., Ltd.

[0098] Blocked isocyanate compounds are compounds having two or more blocked isocyanate groups in the molecule. Blocked isocyanate groups refer to groups obtained by blocking the above-mentioned organic polyisocyanate compounds with blocking agents such as amines, phenols, imines, thiols, pyrazoles, oximes, and active methylene groups. As commercial products thereof, the "Elastron" (registered trademark) series of Daiichi Kogyo Seiyaku Co., Ltd., the "Duranate" (registered trademark) series manufactured by Asahi Kasei Corporation, and the "Takenate" (registered trademark) series manufactured by Mitsui Chemicals, Inc. can be cited.

[0099] Examples of the oxazoline crosslinking agent include compounds having two or more oxazoline groups (oxazoline skeleton) in the molecule, and examples of commercially available products include the "EPOCROS" (registered trademark) series manufactured by Nippon Shokubai Co., Ltd.

[0100] Examples of the carbodiimide crosslinking agent include compounds having two or more carbodiimide groups in the molecule, and examples of commercially available products thereof include "Carbodilite" (registered trademark) series manufactured by Nisshinbo Chemical Co., Ltd., and the like.

[0101] Among the above cross-linking agents, carbodiimide-based cross-linking agents are particularly preferably used because the polyurethane having a hydrophilic group obtained after the reaction has particularly excellent durability and flexibility.

[0102] (1-7) Composition of polyurethane having hydrophilic groups

[0103] From the viewpoint of flexibility, the polyurethane having a hydrophilic group preferably contains constituents derived from polyether polyols. By making the polyurethane having a hydrophilic group contain constituents derived from polyether polyols, since the degree of freedom of the ether bond is high and the glass transition temperature is low, and the cohesive force is also weak, it is possible to prepare a water-dispersible polyurethane with excellent flexibility.

[0104] In addition, the polyurethane with a hydrophilic group preferably further comprises a constituent derived from a polycarbonate-based polyol from the viewpoint of its durability. By making the polyurethane with a hydrophilic group comprise a constituent derived from polycarbonate, the polyurethane with a hydrophilic group can be made into a polyurethane with excellent water resistance, heat resistance, weather resistance, and mechanical properties due to the high cohesive force of its carbonate group.

[0105] It should be noted that as a method for confirming the constituent components of the polyurethane having a hydrophilic group, the polyester ultrafine fibers constituting the artificial leather are eluted from the artificial leather, and the insoluble matter (polyurethane having a hydrophilic group) is analyzed by infrared spectroscopy (as an analytical instrument, for example, "FT / IR 4000 series" manufactured by JASCO Corporation, etc.) and thermal decomposition GC / MS analysis (as an analytical instrument, for example, "GCMS-QP5050A" manufactured by Shimadzu Corporation, etc.), and it can be confirmed that the polyurethane having a hydrophilic group contains constituent components derived from polyester polyol and constituent components derived from polycarbonate polyol. It should be noted that as a solvent capable of dissolving the polyester ultrafine fibers constituting the artificial leather, m-cresol and hexafluoroisopropanol can be used, and hexafluoroisopropanol that can be operated at room temperature is preferably used.

[0106] In addition, the polyurethane with a hydrophilic group used in the present invention preferably has an N-acylurea bond and / or an isourea bond. The N-acylurea bond and / or the isourea bond are formed by the reaction of the hydrophilic group with a cross-linking agent having a carbodiimide group, and a cross-linked structure is formed in the polyurethane with a hydrophilic group, thereby being able to improve the durability of the polyurethane with a hydrophilic group.

[0107] It should be noted that, in the case where the above-mentioned N-acylurea group and isourea group are present in the polyurethane having a hydrophilic group, analysis can be performed by subjecting the cross section of the artificial leather to mapping treatment such as time-of-flight secondary ion mass spectrometry analysis (TOF-SIMS analysis) (as an analytical instrument, for example, "TOF.SIMS 5" manufactured by ION-TOF Corporation, etc.) or infrared spectroscopy analysis (as an analytical instrument, for example, "FT / IR 4000 series manufactured by JASCO Corporation, etc.).

[0108] [Artificial leather]

[0109] The artificial leather of the present invention is an artificial leather comprising the fibrous substrate and the polyurethane having a hydrophilic group as constituent elements. In addition, in the artificial leather of the present invention, the content ratio of the polyurethane having a hydrophilic group in the artificial leather is 15% by mass or more and 25% by mass or less, the mass retention rate of the polyurethane having a hydrophilic group after the artificial leather is immersed in N,N-dimethylformamide at 25°C for 24 hours is 50% by mass or more and 80% by mass or less, and the weight average molecular weight of the component dissolved in the N,N-dimethylformamide after the artificial leather is immersed in N,N-dimethylformamide at 25°C for 24 hours is 50,000 or more and 100,000 or less. By satisfying all of these three conditions, it is possible for the first time to obtain an artificial leather having a soft hand feel and rarely experiencing changes in appearance such as breakage, punctures, and pilling even in extremely high-load wear tests.

[0110] First, the content of the polyurethane having a hydrophilic group in the artificial leather of the present invention is 15% by mass or more and 25% by mass or less. By making the content of the polyurethane having a hydrophilic group 15% by mass or more, preferably 18% by mass or more, an artificial leather having excellent wear resistance can be obtained. On the other hand, by making the content of the polyurethane having a hydrophilic group 25% by mass or less, preferably 22% by mass or less, an artificial leather having a soft hand feel can be obtained.

[0111] In the present invention, the content ratio of the polyurethane having a hydrophilic group is measured and calculated by the following method. That is,

[0112] (1) Cut a 5 cm × 5 cm test piece from the artificial leather and measure the mass (M) of the test piece. X ).

[0113] (2) The test piece was immersed in hexafluoroisopropanol to dissolve the polyester ultrafine fibers from the artificial leather.

[0114] (3) The insoluble component (polyurethane having a hydrophilic group) of (2) was dried in a dryer at 100°C and the mass (M A ), and the content ratio of the polyurethane having a hydrophilic group in the artificial leather was calculated using the following formula.

[0115] The content ratio of polyurethane having hydrophilic groups (%) = (M A / M X )×100.

[0116] In addition, regarding the artificial leather of the present invention, the mass retention rate of the polyurethane having a hydrophilic group after the artificial leather is immersed in N,N-dimethylformamide at 25° C. for 24 hours (hereinafter, sometimes referred to as "the mass retention rate of the polyurethane having a hydrophilic group") is 50% by mass or more and 80% by mass or less. The mass retention rate of the polyurethane having a hydrophilic group is related to the durability and softness of the polyurethane having a hydrophilic group. When the lower limit is 50% by mass or more, preferably 55% by mass or more, and more preferably 60% by mass or more, the polyurethane having a hydrophilic group has a high molecular weight and excellent durability component that is insoluble in N,N-dimethylformamide, and becomes an artificial leather with excellent durability represented by wear resistance. On the other hand, when the upper limit of the mass retention rate of the polyurethane having a hydrophilic group is 80% by mass or less, preferably 75% by mass or less, and more preferably 70% by mass or less, the polyurethane having a hydrophilic group contains a low molecular weight component that is soluble in N,N-dimethylformamide and has an excellent hand feel, thereby providing an artificial leather having a soft and excellent hand feel.

[0117] It should be noted that, in the present invention, the mass retention rate of the polyurethane having a hydrophilic group is measured and calculated by the following method. That is,

[0118] (1) A test piece of 5 cm×5 cm was cut out from artificial leather.

[0119] (2) The test piece was immersed in hexafluoroisopropanol to dissolve the polyester ultrafine fibers from the artificial leather.

[0120] (3) The insoluble component (polyurethane having a hydrophilic group) of (2) was dried in a dryer at 100°C and the mass (M α ) and then immersed in N,N-dimethylformamide at 25°C for 24 hours, and the insoluble components were dried in a dryer at 100°C, and the mass (M β ), and the mass retention rate after immersion in N,N-dimethylformamide for 24 hours was calculated using the following formula.

[0121] Mass retention after immersion in N,N-dimethylformamide for 24 hours (%) = (M β / M α )×100

[0122] (4) The measurement was performed three times, and the arithmetic mean (%) of the obtained values ​​was calculated, and the second decimal place was rounded off.

[0123] In addition, the quality retention rate of the polyurethane with hydrophilic groups can be adjusted by the weight average molecular weight and crosslinking degree of the polyurethane with hydrophilic groups used. For example, the weight average molecular weight of the polyurethane with hydrophilic groups can be adjusted by the weight average molecular weight of the polyurethane precursor used, the atmosphere temperature of the heat treatment, and the treatment time. As the weight average molecular weight increases, the quality retention rate tends to increase; as the crosslinking degree of the polyurethane with hydrophilic groups increases, the quality retention rate tends to increase.

[0124] Moreover, regarding the artificial leather of the present invention, the weight average molecular weight of the component dissolved in N,N-dimethylformamide after the artificial leather is immersed in N,N-dimethylformamide at 25°C for 24 hours (hereinafter, sometimes simply referred to as "the weight average molecular weight of the dissolved component") is 50,000 or more and 100,000 or less. The dissolved component is a component with a lower molecular weight among the polyurethane having a hydrophilic group as a constituent element of the artificial leather, and the "weight average molecular weight of the dissolved component" is substantially equivalent to the weight average molecular weight of the polyurethane precursor used to obtain the polyurethane having a hydrophilic group as a constituent element of the artificial leather. Regarding the range of the weight average molecular weight of the dissolved component, by making the lower limit thereof 50,000 or more, more preferably 60,000 or more, the strength and durability of the polyurethane having a hydrophilic group can be improved. On the other hand, regarding the range, by making the upper limit thereof 100,000 or less, more preferably 90,000 or less, and further preferably 80,000 or less, an artificial leather with a soft hand feel can be obtained.

[0125] It should be noted that in the present invention, the weight average molecular weight of the dissolved component can be determined by immersing the artificial leather in N,N-dimethylformamide at 25° C. for 24 hours, drying the component dissolved in N,N-dimethylformamide, and then performing gel permeation chromatography (GPC). The measurement is performed under the following conditions.

[0126] · Instrument: For example, "HLC-8220" manufactured by Tosoh Corporation

[0127] · Chromatographic column: For example, "TSKgel α-M" manufactured by Tosoh Corporation

[0128] Solvent: N,N-dimethylformamide (DMF)

[0129] Temperature: 40℃

[0130] · Standard sample for calibration: polystyrene (for example, "TSK standard POLYSTYRENE" manufactured by Tosoh Corporation).

[0131] The weight average molecular weight of the dissolved component can be adjusted by the weight average molecular weight of the polyurethane having a hydrophilic group used, the atmosphere temperature of the heat treatment, and the heat treatment time.

[0132] The artificial leather of the present invention preferably has an apparent density of 0.30 g / cm 3 Above 0.40g / cm 3 By making the apparent density of artificial leather 0.30 g / cm 3 More preferably, 0.32 g / cm 3 More preferably, 0.34 g / cm 3 On the other hand, by making the apparent density of the artificial leather 0.40g / cm 3 Below, preferably 0.38 g / cm 3 The following steps can produce artificial leather having a soft touch.

[0133] In the present invention, the apparent density of artificial leather is calculated by measuring the thickness and mass per unit area of ​​artificial leather using the method specified in JIS L1913:2010 "General nonwoven fabric test methods" 6.1.1 (thickness A method) and 6.2 (mass per unit area) and using the following formula.

[0134] Apparent density of artificial leather (g / cm 3 ) = mass per unit area of ​​artificial leather (g / cm 2 ) / thickness of artificial leather (cm).

[0135] The artificial leather of the present invention preferably has a pile of 150 μm or more and 400 μm or less on at least one side. By making the pile length (hereinafter sometimes referred to as "pile length") 150 μm or more, preferably 200 μm or more, an artificial leather having a suede-like beautiful appearance can be produced. On the other hand, by making the pile length 400 μm or less, preferably 350 μm or less, dirt can be suppressed from entering the interior of the pile, and an artificial leather with less contamination and excellent appearance can be produced even in long-term actual use.

[0136] When the artificial leather has pile, the pile length is calculated by the following method.

[0137] (1) Using a lint brush or the like, a cross section of the artificial leather is photographed at a magnification of 50 to 100 times with the pile in an inverted state using a scanning electron microscope (SEM, for example, "VHX-D500 / D510" manufactured by KEYENCE CORPORATION).

[0138] (2) In the SEM images taken, according to Figure 1 The schematic diagram of the cross section of the artificial leather shown is shown in FIG. Figure 1 Medium B )Parallel lines( Figure 1 Medium A Top) Ten vertical lines are drawn at 200 μm intervals.

[0139] (3) Points P1 to P2 are marked on the intersections of the boundary line (L0) between the pile portion (1 in the figure) and the base portion (2 in the figure) other than the pile portion, and the vertical line. 10 .

[0140] (4) For the points P1 to P 10 The points Q1 to Q2 where the vertical lines of the respective 10 Mark it.

[0141] (5) Let the distance between point P1 and Q1 be R1. Similarly, find R2 to R 10 , calculate R1~R 10 The average value (arithmetic mean) is taken as the pile length in the present invention.

[0142] The artificial leather of the present invention preferably has a wear loss of 30 mg or less when measured at 50,000 abrasions in the Martindale abrasion test specified in "8.19 Abrasion strength and friction discoloration" of "8.19.5E method (Martindale method)" of JIS L1096:2005 "Test methods for fabrics of woven and knitted fabrics". From the viewpoint of being able to suppress deterioration of the appearance of the artificial leather, the wear loss is more preferably 25 mg or less.

[0143] It should be noted that the wear loss can be adjusted by making the content ratio of the polyurethane having a hydrophilic group in the artificial leather, the mass retention rate of the polyurethane having a hydrophilic group after the artificial leather is immersed in N,N-dimethylformamide at 25°C for 24 hours, and the density change rate of the non-woven fabric containing ultrafine fiber-developing fibers before and after entanglement within the preferred range described.

[0144] The artificial leather obtained by the present invention can be suitably used as: an interior decoration material having a very beautiful appearance as a surface material for furniture, chairs and wall materials, seats, ceilings and interior decorations in the interiors of vehicles such as automobiles, trains and aircraft; uppers and decorations of shoes such as shirts, jackets, casual shoes, sports shoes, men's shoes and women's shoes; bags, belts, wallets, etc.; and clothing materials used for parts of them; industrial materials such as wiping cloths, polishing cloths and CD curtains.

[0145] [Manufacturing method of artificial leather]

[0146] The method for producing artificial leather of the present invention is preferably a method for producing artificial leather comprising the following steps (1) to (4) in order.

[0147] Step (1): performing an entanglement treatment on a nonwoven fabric containing ultrafine fiber-developing fibers so that the density change rate before and after the entanglement becomes 2.5 times or more and 3.5 times or less to form a fibrous substrate;

[0148] Step (2): impregnating the fibrous substrate with an aqueous dispersion containing a polyurethane precursor having a weight average molecular weight of 50,000 to 100,000 and a crosslinking agent, and then performing a heat drying treatment to form an impregnated sheet containing the fibrous substrate and the polyurethane having a hydrophilic group as constituent elements;

[0149] Step (3): allowing the polyester ultrafine fibers to emerge from the ultrafine fiber-emerging fibers of the impregnated sheet to form a pre-heat-treated sheet comprising a fibrous substrate composed of the polyester ultrafine fibers and a polyurethane having a hydrophilic group as constituent elements;

[0150] Step (4): heat-treating the pre-heat-treatment sheet at an ambient temperature of 150° C. to 200° C. for 5 minutes to 20 minutes.

[0151] The details are described below.

[0152] <Step of Forming a Fibrous Base Material>

[0153] In this step, a nonwoven fabric containing ultrafine fiber-developing fibers is subjected to an entanglement treatment so that the density change rate before and after the entanglement becomes 2.5 times or more and 3.5 times or less to form a fibrous base material.

[0154] As ultrafine fiber-developing fibers, a thermoplastic resin having two components (two or three components in the case where the island fiber is a core-sheath composite fiber) with different solvent solubility is used as a sea component and an island component, and the sea component is dissolved and removed using a solvent or the like to form an ultrafine fiber from the island component, thereby allowing appropriate gaps to be provided between the island components, i.e., between the ultrafine fibers inside the fiber bundle, when the sea component is removed. This is preferred from the viewpoint of the feel and surface quality of the artificial leather.

[0155] As island-in-sea type composite fibers, from the viewpoint of being able to obtain ultrafine fibers with uniform single fiber diameter, it is preferred to use a polymer array body in which two components, namely the sea component and the island component (three components when the island fiber is a core-sheath composite fiber), are arranged and spun using an island-in-sea type composite spinneret.

[0156] As the sea component of the island-in-sea type composite fiber, polyethylene, polypropylene, polystyrene, copolyester obtained by copolymerizing sodium sulfoisophthalic acid or polyethylene glycol, and polylactic acid can be used. From the viewpoint of spinning properties and easy dissolution, polystyrene and copolyester are preferably used.

[0157] The mass ratio of the sea component to the island component in the sea-island type composite fiber used in the present invention is preferably in the range of sea component: island component = 10:90 to 80:20. When the mass ratio of the sea component is 10% by mass or more, the island component is easily fully refined. In addition, when the mass ratio of the sea component is 80% by mass or less, the proportion of the eluted component is small, so the productivity is improved. The mass ratio of the sea component to the island component is more preferably in the range of sea component: island component = 20:80 to 70:30.

[0158] In addition, as the nonwoven fabric constituting the fibrous substrate, as described above, either short-fiber nonwoven fabric or long-fiber nonwoven fabric can be used. In the case of a short-fiber nonwoven fabric, there are more fibers in the thickness direction of the artificial leather than in a long-fiber nonwoven fabric, and a high density can be obtained on the surface of the artificial leather when raised, so it is preferred.

[0159] When a short fiber nonwoven fabric is used as the fibrous substrate, the obtained ultrafine fiber-developing fibers are preferably crimped and cut into a predetermined length to obtain raw cotton. The crimping and cutting processes can be performed by known methods.

[0160] Next, the obtained raw cotton is made into a nonwoven fabric by a cross-lapping machine. Then, for the obtained nonwoven fabric, the apparent density rate of change before and after the complexing is more than 2.5 times and less than 3.5 times to carry out complexing, thereby obtaining a fibrous substrate. By making the apparent density rate of change before and after the complexing more than 2.5 times, more preferably more than 2.7 times, the complexing between fibers becomes sufficient, and the durability improves. On the other hand, by making the apparent density rate of change less than 3.5 times, more preferably less than 3.2 times, it is possible to maintain sufficient space for imparting a polyurethane with a hydrophilic group between fibers. As a method for obtaining a fibrous substrate by complexing a nonwoven fabric, acupuncture treatment, spunlace treatment, etc. can be used, and in order to make the apparent density rate of change before and after the complexing within the above range, it is preferably carried out acupuncture treatment with a high complexing efficiency.

[0161] The apparent density change rate before and after entanglement is an index showing the degree of entanglement of the fibrous substrate and can be calculated by the following formula.

[0162] Apparent density change rate before and after entanglement (fold) = Apparent density of fibrous substrate after entanglement (g / cm 3 ) / Apparent density of nonwoven fabric before entanglement (g / cm 3 )

[0163] Here, the apparent density (g / cm 3 ), the thickness and mass per unit area of ​​the fiber web were measured using the method specified in "6.1 Thickness (ISO method)" and "6.1.1A method" of "6.2 Mass per unit area (ISO method)" of JIS L1913:2010 "General nonwoven fabric test methods", and calculated using the following formula. Here, the fiber web includes both the nonwoven fabric before entanglement and the fibrous substrate after entanglement.

[0164] Apparent density of fiber web (g / cm 3 ) = mass per unit area of ​​the fiber web (g / cm 2 ) / thickness of fiber web (cm).

[0165] In addition, as a method of entanglement of a nonwoven fabric to obtain a fibrous substrate, needle punching, hydroentanglement, etc. can be used. In order to make the apparent density change rate before and after entanglement within the above range, needle punching with high entanglement efficiency is preferably performed.

[0166] In the case of entanglement by needle punching, in order to improve the smoothness of the raw cotton and improve the entanglement efficiency, it is also a preferred embodiment to add 0.01 to 3% by mass of silicone relative to the raw cotton before entanglement. By making the amount of silicone added 0.01% by mass or more, preferably 0.05% by mass or more, the entanglement efficiency can be improved. On the other hand, by making the amount of silicone added 3% by mass or less, more preferably 1% by mass or less, it is possible to suppress the fiber substrate from being greatly elongated during processing and the quality of artificial leather from being reduced.

[0167] In the case of entanglement by needle punching, in order to make the apparent density change rate before and after entanglement the above value, it is preferred to use a needle with barbs (cuts) capable of holding 5 to 15 fibers as the needle used, at a rate of 2000 barbs / cm 2 Above 4000 / cm 2 Acupuncture was performed at the following acupuncture densities.

[0168] The apparent density of the fibrous substrate containing the entangled composite fibers (ultrafine fiber-developing fibers) is preferably 0.20 g / cm 3 Above 0.30g / cm 3 By making the apparent density 0.20 g / cm 3 More preferably, 0.23 g / cm 3 As described above, the fibrous substrate can obtain sufficient morphological stability and dimensional stability. On the other hand, by making the apparent density 0.30 g / cm 3 Below, more preferably 0.28g / cm 3Hereinafter, a sufficient space for providing the polyurethane having a hydrophilic group can be maintained.

[0169] From the viewpoint of densification, it is also a preferred embodiment to shrink the fibrous base material thus obtained by dry heat, wet heat, or both to further increase the density.

[0170] <Step of Forming an Impregnated Sheet>

[0171] In this step, the fibrous substrate is impregnated with an aqueous dispersion containing a polyurethane precursor having a weight average molecular weight of 50,000 to 100,000 and a crosslinking agent, and then subjected to a heat drying treatment to form an impregnated sheet containing the fibrous substrate and the polyurethane having a hydrophilic group as constituent elements.

[0172] The concentration of the polyurethane precursor in the aqueous dispersion (the content of the polyurethane precursor in 100% by mass of the aqueous dispersion) is preferably 3% by mass or more and 30% by mass or less. By setting the concentration to 3% by mass or more, more preferably 5% by mass or more, the polyurethane precursor can be uniformly applied to the fibrous substrate even when the amount of the polyurethane precursor applied is small. On the other hand, by setting the concentration to 30% by mass or less, more preferably 15% by mass or less, the storage stability of the aqueous dispersion can be improved.

[0173] It is important that the weight average molecular weight of the polyurethane precursor used in the present invention is 50,000 or more and 100,000 or less. By making the weight average molecular weight 50,000 or more, more preferably 60,000 or more, the strength and durability of the polyurethane having a hydrophilic group can be improved. On the other hand, by making the weight average molecular weight 100,000 or less, more preferably 90,000 or less, and further preferably 80,000 or less, an artificial leather with a soft hand feel can be produced.

[0174] In the present invention, the weight average molecular weight of the polyurethane precursor can be measured by the same method as the weight average molecular weight of the above-mentioned dissolved component.

[0175] After the aqueous dispersion is impregnated into the fibrous substrate, coagulation can be performed using a coagulation method commonly used in the art, such as a dry heat coagulation method or a liquid coagulation method. When the dry heat coagulation method is used, it is preferred that after the aqueous dispersion is applied to the fibrous substrate, a heat treatment is performed at a temperature of 120° C. to 180° C. to perform dry heat coagulation, thereby providing the fibrous substrate with a polyurethane having a hydrophilic group. In addition, when the liquid coagulation method is used, an acid coagulation method using a coagulation solvent having a pH of 1 to 3 or a hot water coagulation method using hot water having a temperature of 80° C. to 100° C. can be used.

[0176] In the method for producing artificial leather of the present invention, when a dry heat coagulation method is used, the aqueous dispersion may contain an inorganic salt. By containing an inorganic salt, the aqueous dispersion can be given thermosensitive coagulation properties. In the present invention, thermosensitive coagulation properties refer to the property that when the aqueous dispersion is heated, when a certain temperature (thermosensitive coagulation temperature) is reached, the fluidity of the aqueous dispersion decreases and coagulation occurs.

[0177] The thermosensitive coagulation temperature of the aqueous dispersion is preferably 55° C. to 80° C. The thermosensitive coagulation temperature is 55° C. or higher, more preferably 60° C. or higher, so that gelation during preparation and storage of the aqueous dispersion can be suppressed. On the other hand, by setting the thermosensitive coagulation temperature to 80° C. or lower, more preferably 70° C. or lower, the coagulation of the polyurethane precursor proceeds before the water evaporates from the fibrous substrate, thereby forming a structure similar to that obtained by wet coagulation of a solvent-based polyurethane, that is, a structure in which the polyurethane does not firmly bind the fibers, and good softness and resilience can be achieved.

[0178] In the present invention, when an inorganic salt is used as a thermosensitive coagulant, an inorganic salt containing a univalent cation is preferably used. The inorganic salt containing a univalent cation is preferably sodium chloride and / or sodium sulfate. An inorganic salt containing a univalent cation with a small ion valence has a small effect on the stability of the aqueous dispersion. By adjusting the addition amount, the stability of the aqueous dispersion can be ensured, and the thermosensitive coagulation temperature can be strictly controlled.

[0179] Furthermore, in the present invention, the content of the inorganic salt containing monovalent cations in the aqueous dispersion is preferably 10% by mass or more and 50% by mass or less relative to the polyurethane precursor. By making the content 10% by mass or more, more preferably 20% by mass or more, and further preferably 30% by mass or more, the ions present in a large amount in the aqueous dispersion act uniformly on the polyurethane precursor particles, thereby being able to quickly complete coagulation at a specific thermosensitive coagulation temperature. Thus, as described above, it is possible to obtain a more significant effect in coagulation of the polyurethane precursor in a state where a large amount of water is contained in the fibrous substrate. As a result, a structure very similar to that obtained by wet coagulation of solvent-based polyurethane is formed, and good softness and resilience can be achieved. Furthermore, by making the addition amount as described above, the inorganic salt becomes an inhibitor of the welding of the particles of the polyurethane precursor, and the curing of the polyurethane precursor caused by the continuous formation of the coating can also be suppressed. On the other hand, by making the content 50% by mass or less, the continuous coating structure of the appropriate polyurethane precursor remains, which can suppress the reduction of physical properties. In addition, the stability of the aqueous dispersion can also be maintained.

[0180] In the method for producing artificial leather of the present invention, it is important to include a crosslinking agent in the aqueous dispersion. By introducing a three-dimensional network structure into the polyurethane precursor using a crosslinking agent, physical properties such as abrasion resistance can be improved.

[0181] The concentration of the crosslinking agent in the aqueous dispersion is preferably set to 1% by mass or more and 10% by mass or less relative to the mass of the polyurethane precursor. By setting the concentration of the crosslinking agent in the aqueous dispersion to 1% by mass or more, more preferably 2% by mass or more, the three-dimensional mesh structure can be introduced more into the polyurethane precursor by the crosslinking agent, and an artificial leather having excellent wear resistance and the like can be obtained. On the other hand, by setting the concentration of the crosslinking agent to 10% by mass or less, more preferably 7% by mass or less, when the polyurethane precursor is formed, the excess crosslinking agent is suppressed from hindering the coagulation of the polyurethane precursor, and the reduction of physical properties such as wear resistance can be easily suppressed.

[0182] The crosslinking agent involved in the method for producing artificial leather of the present invention is preferably a carbodiimide crosslinking agent and / or a blocked isocyanate crosslinking agent. Thus, a three-dimensional crosslinking structure can be given to the molecules of the polymer elastomer in the artificial leather by utilizing N-acylurea bonds and / or isourea bonds which are excellent in physical properties such as light resistance, heat resistance, and abrasion resistance, as well as flexibility, so that physical properties such as durability and abrasion resistance can be greatly improved while maintaining the flexibility of the artificial leather.

[0183] Then, after being impregnated with the aqueous dispersion, a heat drying treatment is performed to form an impregnated sheet including a fibrous base material and a polyurethane having a hydrophilic group as constituent elements.

[0184] The temperature of the heating and drying treatment after the immersion in the aqueous dispersion is preferably 110°C or higher, and more preferably 120°C or higher. By setting the temperature of the heating and drying treatment to 110°C or higher, not only the drying efficiency of the sheet can be improved, but also the cross-linking reaction can be promoted, and artificial leather with higher physical properties such as durability and wear resistance can be obtained. On the other hand, by setting the temperature of the heating and drying treatment to 180°C or lower or 170°C or lower, thermal degradation of the polyurethane having a hydrophilic group can be suppressed.

[0185] The time of the heating and drying treatment is preferably 5 minutes or more and 30 minutes or less. By heating for 5 minutes or more, more preferably 10 minutes or more, the crosslinking reaction can be promoted. By setting the heating time to 30 minutes or less, preferably 25 minutes or less, the thermal degradation of the polyurethane having a hydrophilic group caused by excessive heating can be suppressed.

[0186] <Step of Forming a Sheet Before Heat Treatment>

[0187] In this step, the polyester ultrafine fibers are developed from the ultrafine fiber-developing fibers of the impregnated sheet to form a pre-heat-treated sheet including a fibrous base material composed of the polyester ultrafine fibers and polyurethane having a hydrophilic group as constituent elements.

[0188] When the sea-island type composite fiber is used as the ultrafine fiber-developing fiber, the fiber ultrafine treatment (sea removal treatment) can be performed, for example, by immersing the sea-island type composite fiber in a solvent and then heating it. The solvent for dissolving the sea component can be appropriately selected according to the type of the sea component. When the sea component is a copolyester, an alkaline aqueous solution such as an aqueous sodium hydroxide solution can be used.

[0189] When an alkaline aqueous solution is used as a solvent for the sea removal treatment, the molar concentration of the alkaline aqueous solution is preferably 3 mol / L or less in order to prevent excessive deterioration of the polyurethane having a hydrophilic group.

[0190] <Heat treatment process>

[0191] In this step, the pre-heat treatment sheet is heat-treated at an ambient temperature of 150° C. to 200° C. for 5 minutes to 20 minutes.

[0192] This heat treatment is performed after obtaining the pre-heat-treated sheet, and is preferably performed immediately after the ultrafine fiberization treatment in order to suppress quality degradation due to elongation during the process.

[0193] As a method for heat treatment, a hot air dryer such as a float dryer, a drum dryer, or a pin tenter is preferably used.

[0194] In this heat treatment, it is important to set the atmosphere temperature to 150° C. to 200° C. and the heating time to 5 minutes to 20 minutes. This improves the adhesion between the ultrafine fibers and the polyurethane having a hydrophilic group, thereby improving the strength and abrasion resistance of the artificial leather, and softens the artificial leather by lowering the molecular weight of a portion of the polyurethane having a hydrophilic group, thereby achieving an artificial leather having both a soft feel and excellent abrasion resistance.

[0195] First, it is important to set the atmosphere temperature to 150°C or higher and 200°C or lower. By setting the temperature to 150°C or higher, more preferably 155°C or higher, the adhesion between the ultrafine fibers and the polyurethane having a hydrophilic group is improved, which can not only improve the strength and abrasion resistance of the artificial leather, but also reduce the molecular weight of a part of the polyurethane having a hydrophilic group to improve the softness of the artificial leather. On the other hand, by setting the temperature to 200°C or lower, preferably 190°C or lower, more preferably 180°C or lower, a part of the polyurethane having a hydrophilic group can be gradually reduced in molecular weight.

[0196] Secondly, it is important to set the heating time to be between 5 minutes and 20 minutes. By setting the heating time to be between 5 minutes and 6 minutes, the adhesion between the ultrafine fibers and the polyurethane having a hydrophilic group is improved, and the strength and abrasion resistance of the artificial leather can be improved. On the other hand, by setting the heating time to be between 20 minutes and 20 minutes, preferably between 15 minutes and 12 minutes, it is possible to prevent the physical properties of the artificial leather from being reduced due to excessive molecular weight reduction of the polyurethane having a hydrophilic group.

[0197] <Finishing process>

[0198] In the method for producing artificial leather of the present invention, it is also preferred to perform various finishing steps similarly to general artificial leather.

[0199] First, the manufacture method of artificial leather of the present invention preferably comprises the dyeing process of dyeing artificial leather.As this dyeing process, can adopt the various methods commonly used in this field.For example, can use: the liquid flow dyeing process using the jigger, liquid flow dyeing machine, the thermosol dyeing process using the continuous dyeing machine, etc., or the printing and dyeing process to the suede surface based on drum printing and dyeing, screen printing and dyeing, inkjet printing and dyeing, sublimation printing and dyeing and vacuum sublimation printing and dyeing, etc.Wherein, owing to be able to give the rubbing effect while dyeing unhaired artificial leather or artificial leather and make unhaired artificial leather or artificial leather soften, therefore preferably use liquid flow dyeing machine.In addition, according to need, can implement various resin finishing after dyeing.

[0200] In addition, a finishing agent treatment can be applied in the same bath as dyeing or after dyeing. For example, a softener such as silicone, an antistatic agent, a water repellent, a flame retardant, a light fastness agent, an antibacterial agent, etc. are used in the finishing agent treatment.

[0201] In the present invention, from the viewpoint of production efficiency, half-cutting in the thickness direction is also a preferred embodiment regardless of whether it is before or after the dyeing step.

[0202] The method for producing artificial leather of the present invention preferably includes a raising step for forming pile, either before or after the dyeing step. The method for forming the pile is not particularly limited, and various methods commonly used in the art such as polishing with sandpaper or the like can be used.

[0203] When the napping treatment is performed, a lubricant such as a silicone emulsion may be applied to the surface of the artificial leather before the napping treatment. In addition, by applying an antistatic agent before the napping treatment, grinding powder generated from the artificial leather by grinding is less likely to accumulate on the sandpaper. In this way, the artificial leather is formed.

[0204] Furthermore, in the method for producing artificial leather of the present invention, the artificial leather may be subjected to post-processing such as perforation or other hole-forming processing, embossing processing, laser processing, ultrasonic thermal bonding processing, and printing processing as required.

[0205] Example

[0206] The artificial leather of the present invention will be further specifically described using Examples, but the present invention is not limited to these Examples.

[0207] [Evaluation method]

[0208] The evaluation methods and measurement conditions used in the examples are described below. In addition, in the measurement of each physical property, unless otherwise specified, the measurement was performed according to the above-mentioned method.

[0209] (1) Average single fiber diameter (μm):

[0210] The average single fiber diameter (μm) was measured and calculated by the above-mentioned method using “VHX-D500 / D510” manufactured by KEYENCE CORPORATION as a scanning electron microscope (SEM).

[0211] (2) Weight average molecular weight of polyurethane precursor and dissolved components (unitless):

[0212] The weight average molecular weight of the polyurethane precursor or the dissolved component was measured and calculated by the above-mentioned method using the following apparatus and under the following conditions.

[0213] · Instrument: HLC-8020 (manufactured by Tosoh Corporation)

[0214] ·Chromatographic column: TSKgel GMH-XL (manufactured by Tosoh Corporation)

[0215] Solvent: N,N-dimethylformamide (DMF)

[0216] Temperature: 40℃

[0217] · Calibration standard sample: Polystyrene ("TSK standard POLYSTYRENE" manufactured by Tosoh Corporation)

[0218] Flow rate: 1.0 ml / min.

[0219] (3) Confirmation that the polyurethane having a hydrophilic group has an N-acylurea bond and / or an isourea bond

[0220] The infrared spectroscopic analysis was performed using the "FT / IR 4600" manufactured by JASCO Corporation. A 5 cm x 5 cm test piece was cut from the artificial leather and immersed in hexafluoroisopropanol to dissolve the polyester microfibers from the artificial leather. The insoluble components (polyurethane with hydrophilic groups) were then dried in a dryer at 100°C and then analyzed by infrared spectroscopy. The results showed that the polyester microfibers were not soluble in water at 1650 cm. -1 When a peak derived from C═O stretching vibration of an N-acylurea bond and / or an isourea bond is observed nearby, it is determined that the polyurethane having a hydrophilic group has an N-acylurea bond and / or an isourea bond.

[0221] (4) Content ratio of polyurethane having hydrophilic group (mass %):

[0222] The content ratio (mass %) of the polyurethane having a hydrophilic group is measured and calculated by the above-mentioned method.

[0223] (5) Mass retention rate of polyurethane with hydrophilic groups (%):

[0224] The mass retention rate (%) of the polyurethane having a hydrophilic group was measured and calculated by the above-mentioned method.

[0225] (6) Apparent density of artificial leather (g / cm 3 ):

[0226] About the apparent density of artificial leather (g / cm 3 ), using the "Dial Thickness Gauge Model H" manufactured by Ozaki Manufacturing Co., Ltd. as a thickness gauge, and measuring and calculating by the above method.

[0227] (7) Pile length (μm):

[0228] The pile length was measured and calculated by the above-mentioned method using "VHX-D500 / D510" manufactured by KEYENCE CORPORATION as a scanning electron microscope (SEM).

[0229] (8) Wear loss of artificial leather (mg):

[0230] When measuring and calculating the wear loss (mg) of artificial leather, "Model 406" manufactured by James H.Heal & Co. was used as a Martindale wear tester, and "ABRASTIVE CLOTH SM25" manufactured by the same company was used as a standard friction cloth. Then, a load of 12 kPa was applied to the artificial leather, and the number of wears was set to 50,000 times. The wear loss was calculated using the following formula using the mass of the artificial leather before and after wear.

[0231] Wear loss (mg) = mass before wear (mg) - mass after wear (mg)

[0232] In addition, the wear loss (mg) is a value obtained by rounding off the first decimal place.

[0233] (9) The feel of artificial leather

[0234] Twenty healthy adults were used as evaluators to evaluate the feel of the artificial leather as A, B, or C as follows, and the highest evaluation was used as the touch of the artificial leather. In the present invention, a good level is "A or B".

[0235] A: There is no resistance when holding it, it is soft

[0236] B: There is a slight resistance when holding it, and it is soft

[0237] C: There is a strong sense of resistance when gripping and it is hard.

[0238] [Polyurethane precursor]

[0239] The polyurethane precursors used in Examples and Comparative Examples are as follows.

[0240] PU-A: A polyurethane precursor having a weight average molecular weight of 80,000, using polytetramethylene glycol as a polymer polyol, MDI as an organic diisocyanate, 2,2-dimethylolpropionic acid as a compound having an active hydrogen component having a hydrophilic group, and ethylene glycol as a chain extender.

[0241] PU-B: A polyurethane precursor having a weight average molecular weight of 55,000, using polytetramethylene glycol as a polymer polyol, MDI as an organic diisocyanate, 2,2-dimethylolpropionic acid as a compound having an active hydrogen component having a hydrophilic group, and ethylene glycol as a chain extender.

[0242] PU-C: A polyurethane precursor having a weight average molecular weight of 90,000, using polytetramethylene glycol as a polymer polyol, MDI as an organic diisocyanate, 2,2-dimethylolpropionic acid as a compound having an active hydrogen component having a hydrophilic group, and ethylene glycol as a chain extender.

[0243] PU-D: A polyurethane precursor having a weight average molecular weight of 80,000, using a polyol obtained by copolymerizing polytetramethylene glycol and polyhexamethylene carbonate in a molar ratio of 3:1 as a high molecular weight polyol, MDI as an organic diisocyanate, 2,2-dimethylolpropionic acid as a compound containing an active hydrogen component having a hydrophilic group, and ethylene glycol as a chain extender.

[0244] PU-E: A polyurethane precursor having a weight average molecular weight of 110,000, using polytetramethylene glycol as a polymer polyol, MDI as an organic diisocyanate, 2,2-dimethylolpropionic acid as a compound having an active hydrogen component having a hydrophilic group, and ethylene glycol as a chain extender.

[0245] [Example 1]

[0246] <Step of Forming a Fibrous Base Material>

[0247] Using polyester obtained by copolymerization with 8 mol% of sodium 5-sulfonate of isophthalic acid as the sea component, polyethylene terephthalate with an intrinsic viscosity of 0.73 as the island component, and a spinneret for sea-island composite with 16 islands / hole, melt spinning was performed under the conditions of spinning temperature of 285°C, island / sea mass ratio of 80 / 20, ejection amount of 1.6 g / min·hole, and spinning speed of 1100 m / min. Then, the obtained fiber was stretched to 3.7 times in an oil liquid bath, and 0.5% by mass of dimethyl silicone was added relative to the fiber mass (hereinafter, recorded as "the amount of silicone added relative to the raw cotton" is 0.5% by mass), and then cut into a length of 51 mm to obtain raw cotton of sea-island composite fiber with a single fiber fineness of 3.8 dtex. Then, the raw cotton of the above-mentioned sea-island composite fiber was used and formed into a raw cotton with an apparent density of 0.09 g / cm through the carding and cross-lapping process. 3 A layered net was used. A needle with barbs capable of holding up to 10 raw cotton strands (hereinafter referred to as "the maximum number of barbs held by the needle" is 10 strands) was used at 3500 strands / cm 2 The laminated web is needle-punched at a needle-punching density of 700 g / m 2 , thickness is 2.6mm, apparent density is 0.27g / cm 3 The obtained fibrous substrate was immersed in hot water at 98°C for 2 minutes to shrink it, and then dried at 100°C for 5 minutes to obtain a fibrous substrate of a nonwoven fabric containing sea-island type composite fibers.

[0248] <Step of Forming an Impregnated Sheet>

[0249] As a polyurethane precursor, an aqueous dispersion containing 11 parts by mass of "PU-A", 1 part by mass of a crosslinking agent A (carbodiimide crosslinking agent, "Carbodilite V-02-L2" manufactured by Nisshinbo Chemical Co., Ltd.), 5 parts by mass of sodium sulfate, and 83 parts by mass of water was prepared. After the fibrous substrate was impregnated with the aqueous dispersion, it was squeezed with a liquid squeezer so that the liquid squeeze rate of the aqueous dispersion became 200%, and then heated with hot air at 120° C. for 20 minutes to solidify the polyurethane precursor and form a crosslinked structure containing N-acylurea bonds and / or isourea bonds, thereby obtaining a nonwoven fabric containing sea-island type composite fibers and an impregnated sheet of polyurethane having a hydrophilic group.

[0250] <Step of Forming a Sheet Before Heat Treatment>

[0251] After immersing the obtained impregnated sheet in a 5% sodium hydroxide aqueous solution, it is squeezed with a squeezer in such a way that the squeeze rate of the sodium hydroxide aqueous solution becomes 100%, and then heat-treated with 95°C steam for 10 minutes to alkaline decompose the sea component of the island-in-sea type composite fiber, and then the remaining sodium hydroxide and sodium sulfate are washed with water to obtain a sheet before heat treatment.

[0252] <Heat treatment process>

[0253] The washed sheet before heat treatment was heat treated for 10 minutes using a pin tenter in which the atmosphere temperature was raised to 160° C., thereby obtaining a sheet including a fibrous base material having ultrafine fibers and a polyurethane having a hydrophilic group.

[0254] <Finishing process>

[0255] The obtained sheet was cut in half in a direction perpendicular to the thickness direction, and the opposite side of the half-cut surface was ground with a circular sandpaper of sandpaper No. 120, thereby obtaining a pile sheet with a thickness of 0.70 mm.

[0256] The obtained pile sheet was dyed black with disperse dyes using a liquid jet dyeing machine at a temperature of 120°C. The dyed pile sheet was dried with a dryer to obtain an artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23% by mass of polyurethane having a hydrophilic group. The obtained artificial leather had a soft feel and excellent durability. The results are shown in Table 1.

[0257] [Example 2]

[0258] In the <Step of Forming an Impregnated Sheet>, except that the polyurethane precursor was changed to "PU-B", an artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23% by mass of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1. The obtained artificial leather had a soft feel and excellent durability. The results are shown in Table 1.

[0259] [Example 3]

[0260] In the <Step of Forming an Impregnated Sheet>, except that the polyurethane precursor was changed to "PU-C", an artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23% by mass of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1. The obtained artificial leather had a slight sense of resistance but had a soft feel and excellent durability. The results are shown in Table 1.

[0261] [Example 4]

[0262] In the <Step of Forming an Impregnated Sheet>, except that the liquid extraction rate of the aqueous dispersion was changed to 150%, an artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 18% by mass of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1. The obtained artificial leather had a soft feel and excellent durability. The results are shown in Table 1.

[0263] [Example 5]

[0264] In the <Step of Forming an Impregnated Sheet>, except that the polyurethane precursor was changed to "PU-D", an artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23% by mass of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1. The obtained artificial leather had a slight sense of resistance but had a soft feel and excellent durability. The results are shown in Table 1.

[0265] [Example 6]

[0266] In the <heat treatment step>, except that the heat treatment atmosphere temperature was changed to 180° C., an artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23% by mass of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1. The obtained artificial leather had a soft feel and excellent durability. The results are shown in Table 1.

[0267] [Example 7]

[0268] In the <heat treatment step>, except that the heat treatment time was changed to 15 minutes, an artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23% by mass of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1. The obtained artificial leather had a soft feel and excellent durability. The results are shown in Table 2.

[0269] [Example 8]

[0270] In the <heat treatment step>, except that the heat treatment atmosphere temperature was changed to 150° C., an artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23% by mass of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1. The obtained artificial leather had a slight sense of resistance but had a soft feel and excellent durability. The results are shown in Table 2.

[0271] [Example 9]

[0272] In the <Step of Forming a Fibrous Base Material>, except that dimethyl silicone was not applied to the raw cotton, an artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23% by mass of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1. The obtained artificial leather had a soft feel and excellent durability. The results are shown in Table 2.

[0273] [Example 10]

[0274] In the step of forming a fibrous substrate, dimethyl silicone was not applied to the raw cotton, and 3000 fibers / cm 2 Artificial leather having an average single fiber diameter of 4.4 μm and containing 23% by mass of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1 except that the needle punching was performed with a needle punching number of 10000. The obtained artificial leather had a soft feel and excellent durability. The results are shown in Table 2.

[0275] [Comparative Example 1]

[0276] In the <heat treatment step>, except that the heat treatment time was changed to 30 minutes, an artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23% by mass of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1. The obtained artificial leather had a soft feel, but the durability was greatly reduced. The results are shown in Table 3.

[0277] [Comparative Example 2]

[0278] In the <Step of Forming an Impregnated Sheet>, except that the polyurethane precursor was changed to "PU-E", an artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23% by mass of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1. The obtained artificial leather had excellent durability but had a hard feel. The results are shown in Table 3.

[0279] [Comparative Example 3]

[0280] In the <Step of Forming an Impregnated Sheet>, except that the liquid extraction rate of the aqueous dispersion was changed to 110%, an artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 13% by mass of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1. The obtained artificial leather had a soft feel, but the durability was greatly reduced. The results are shown in Table 3.

[0281] [Comparative Example 4]

[0282] In the <Step of Forming an Impregnated Sheet>, except that the liquid extraction rate of the aqueous dispersion was changed to 250%, an artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 29% by mass of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1. The obtained artificial leather had excellent durability but had a hard feel. The results are shown in Table 3.

[0283] [Comparative Example 5]

[0284] In the step of forming a fibrous substrate, dimethyl silicone was not applied to the raw cotton, and 2500 fibers / cm 2 In the same manner as in Comparative Example 1, except that the needle punching treatment was performed with the number of needle punches of , an artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23% by mass of polyurethane having a hydrophilic group was obtained. The obtained artificial leather had a soft feel, but the durability was greatly reduced. The results are shown in Table 4.

[0285] [Comparative Example 6]

[0286] In the step of forming a fibrous substrate, except that a needle having a "maximum number of needle barbs" of 6 was used as the needle used for needling, an artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23% by mass of polyurethane having a hydrophilic group was obtained in the same manner as in Comparative Example 5. The obtained artificial leather had a soft feel, but the durability was greatly reduced. The results are shown in Table 4.

[0287] [Comparative Example 7]

[0288] In the <heat treatment step>, except that the heat treatment time was changed to 3 minutes, an artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23% by mass of polyurethane having a hydrophilic group was obtained in the same manner as in Example 2. The obtained artificial leather had a soft feel, but the durability was greatly reduced. The results are shown in Table 4.

[0289] [Table 1]

[0290]

Table 1

[0291]

[0292] [Table 2]

[0293]

Table 2

[0294]

[0295] [Table 3]

[0296]

Table 3

[0297]

[0298] [Table 4]

[0299]

Table 4

[0300]

[0301] Description of Reference Numerals

[0302] 1: Pile head

[0303] 2: Base part

Claims

1. Artificial leather comprising a fibrous substrate composed of polyester ultrafine fibers having an average single fiber diameter of 0.1 μm or more and 10.0 μm or less, and a polyurethane having a hydrophilic group as constituent elements, wherein: The content ratio of the polyurethane having a hydrophilic group in the artificial leather is not less than 15 mass % and not more than 25 mass %, the mass retention rate of the polyurethane having a hydrophilic group after the artificial leather is immersed in N,N-dimethylformamide at 25° C. for 24 hours is not less than 50 mass % and not more than 80 mass %, and the weight average molecular weight of the component dissolved in N,N-dimethylformamide after the artificial leather is immersed in N,N-dimethylformamide at 25° C. for 24 hours is not less than 50,000 and not more than 100,000.

2. The artificial leather according to claim 1, wherein The apparent density of artificial leather is 0.30g / cm 3 Above 0.40g / cm 3 the following.

3. The artificial leather according to claim 1 or 2, wherein: The polyurethane having a hydrophilic group includes a constituent component derived from a polyester polyol.

4. The artificial leather according to claim 3, wherein: The polyurethane having a hydrophilic group further includes a constituent component derived from a polycarbonate polyol.

5. The artificial leather according to claim 1 or 2, wherein: The polyurethane having a hydrophilic group has an N-acylurea bond and / or an isourea bond.

6. The method for producing artificial leather according to claim 1, comprising the following steps (1) to (4) in sequence: Step (1): performing an entanglement treatment on a nonwoven fabric containing ultrafine fiber-developing fibers so that the density change rate before and after the entanglement becomes 2.5 times or more and 3.5 times or less to form a fibrous substrate; Step (2): impregnating the fibrous substrate with an aqueous dispersion containing a polyurethane precursor having a weight average molecular weight of 50,000 to 100,000 and a crosslinking agent, and then performing a heat drying treatment to form an impregnated sheet containing the fibrous substrate and the polyurethane having a hydrophilic group as constituent elements; Step (3): allowing the polyester ultrafine fibers to emerge from the ultrafine fiber-emerging fibers of the impregnated sheet to form a pre-heat-treated sheet comprising a fibrous substrate composed of the polyester ultrafine fibers and the polyurethane having a hydrophilic group as constituent elements; Step (4): heat-treating the pre-heat-treatment sheet at an ambient temperature of 150° C. to 200° C. for 5 minutes to 20 minutes.

7. The method for producing artificial leather according to claim 6, wherein: The cross-linking agent is a carbodiimide cross-linking agent.

8. The method for producing artificial leather according to claim 6 or 7, wherein: In the step (1), silicone is added in an amount of 0.01% by mass to 3% by mass based on the mass of the ultrafine fiber-developing fiber.

Citation Information

Patent Citations

  • Method for producing microfibrous suede non-woven fabric and method related to the same

    JP2003306878A

  • Method for manufacturing sheet-shaped object and sheet-shaped object obtained via said method

    WO2014042241A1

  • Sheet material and method for producing same

    WO2021125029A1

  • Sheet-like article and method for producing same

    WO2021125032A1